Pflege-Report 2019 - Antje Schwinger (Springer Nature, 2020)
More staff in long-term care - but where from? The Nursing Report, published in book form and as an open access publication, examines relevant topics for the care of those in need of care annually. The focus of the year 2019 is the question "More staff - but where from?" Different measures are analyzed, which are to ensure a quantitatively as well as qualitatively sufficient supply of nursing staff.